Effect of Vertical Growth Pattern on Maxillary and Frontal Sinus Sizes - Göymen, Merve; Bilgin Büyüknacar, Güzin; Güleç, Ayşegül (European Journal of Therapeutics, 2023)
Objective: The purpose of the present study was to investigate the frontal and maxillary sinus sizes of individuals with different vertical growth pattern by using lateral and posteroanterior (PA) cephalometric radiographs. Methods: In the study conducted on 60 individuals selected from male and female patients between the ages of 15 and 17 years, lateral and PA cephalometric radiographs were divided into three groups by vertical skeletal classification. The radiographs of 20 patients with increased vertical growth [Sella–Nasion Plane and Gonion–Gnathion Plane (Sn–GoGn) >38°] were classified as Group 1, the radiographs of 20 patients with decreased vertical growth (Sn–GoGn <26°) were classified as Group 2, and the radiographs of 20 patients with normal growth (Sn–GoGn: 32±6°) were classified as Group 3. The measurements of maxillary and frontal sinus sizes were obtained via ImageJ software. Results: The differences between the groups for all measurements in both lateral and PA radiographs (p>0.005) were not statistically significant. Conclusion: The different vertical growth pattern was not effective on maxillary and frontal sinus sizes. Future controlled trials conducted with larger samples are needed to support and extend the findings.